The emergence of an independent Polish state and the problem of national minorities - G. G. Dedurin (Bulletin of Kharkiv National University of Internal Affairs)
The main approaches to the regulation of the status of national minorities in the Polish state restored after the First World War were investigated. They were reflected in the relevant provisions of the first Constitution of independent Poland (March 1921), which was a kind of compromise between the views of the Polish right-wing led by Roman Dmowski, who advocated the absolute dominance of ethnic Poles' interests, and the leaders of Polish socialist parties (T. Goluwko, L. Wasilewski), who wanted to support the national and cultural inspirations of minorities in exchange for their loyalty to the Polish state.